NADPH oxidase elevations in pyramidal neurons drive psychosocial stress-induced neuropathology - Schiavone, S (Nature Publishing Group, 2012)
Oxidative stress is thought to be involved in the development of behavioral and histopathological alterations in animal models of psychosis. Here we investigate the causal contribution of reactive oxygen species generation by the phagocyte NADPH oxidase NOX2 to neuropathological alterations in a rat model of chronic psychosocial stress. In rats exposed to social isolation, the earliest neuropathological alterations were signs of oxidative stress and appearance of NOX2. Alterations in behavior, increase in glutamate levels and loss of parvalbumin were detectable after 4 weeks of social isolation. The expression of the NOX2 subunit p47(phox) was markedly increased in pyramidal neurons of isolated rats, but below detection threshold in GABAergic neurons, astrocytes and microglia. Rats with a loss of function mutation in the NOX2 subunit p47(phox) were protected from behavioral and neuropathological alterations induced by social isolation. To test reversibility, we applied the antioxidant/NOX inhibitor apocynin after initiation of social isolation for a time period of 3 weeks. Apocynin reversed behavioral alterations fully when applied after 4 weeks of social isolation, but only partially after 7 weeks. Our results demonstrate that social isolation induces rapid elevations of the NOX2 complex in the brain. Expression of the enzyme complex was strongest in pyramidal neurons and a loss of function mutation prevented neuropathology induced by social isolation. Finally, at least at early stages, pharmacological targeting of NOX2 activity might reverse behavioral alterations.